2012
DOI: 10.1038/jid.2012.24
|View full text |Cite
|
Sign up to set email alerts
|

Dickkopf 1 Promotes Regression of Hair Follicles

Abstract: Recently, we suggested that Dickkopf 1 (DKK-1) is a pathogenic mediator involved in male pattern baldness. As premature catagen onset is a key characteristic of male pattern baldness, in this study, we evaluated whether DKK-1 has a role as a catagen inducer in hair cycling. Herein, we report that recombinant human DKK-1 (rhDKK-1) injection into the hypodermis of mice during anagen caused premature onset of catagen, whereas neutralizing DKK-1 antibody delayed anagen-to-catagen transition in mice. Moreover, trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 32 publications
9
115
1
Order By: Relevance
“…In nonbald "normal" DP cell samples, we found that WNT signaling was lowered but still activated in bald DP samples. DKK1 was suggested as one of the key player of triggering catagen in AGA [45]. We could not detect significant DE of DKK1 in dataset 1.…”
Section: Cross-talk Between Pathways Affected In Aga Dp Cellsmentioning
confidence: 41%
See 3 more Smart Citations
“…In nonbald "normal" DP cell samples, we found that WNT signaling was lowered but still activated in bald DP samples. DKK1 was suggested as one of the key player of triggering catagen in AGA [45]. We could not detect significant DE of DKK1 in dataset 1.…”
Section: Cross-talk Between Pathways Affected In Aga Dp Cellsmentioning
confidence: 41%
“…In human bulge cells, increased expression of the WNT inhibitors WIF1 and DKK3 was also shown [60]. In patients with AGA, dermal papilla cells were shown to produce excessive amounts of factors inhibiting WNT signaling (for instance, DKK1) [45].…”
Section: Bulge Stem Cells Renewal Pathwaymentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been suggested that Dkk1 expression in keratinocytes is involved in the hair follicle transition from anagen to catagen. Injection of recombinant human Dkk1 in mouse skin was found to induce catagen in hair follicle keratinocytes, by blocking Wnt signalling and upregulating expression of Bcl-2-associated X protein (Bax), a promoter of apoptosis, resulting in apoptosis of ORS keratinocytes (Kwack et al, 2012b).…”
Section: Hair Follicle Maintenance and Cyclingmentioning
confidence: 99%